Ameliorating Heat Transfer Performance of Absorber Tube for Single Axis Concentrators. (2016) - Kalidasan, B.; Boopalan, N.; Shankar, R.; Srinivas, T.
Abstract: Solar parabolic trough collectors are being widely used to exploit solar energy for both thermal and power generation applications. But, these systems require long arrays of reflective troughs with absorber tube running along the axis of parabolic dish. A successful attempt to reduce the length of arrays was accomplished by experimentally analysing the modifications done in absorber tube. Three out of four tubes were fabricated and they were employed to obtain the performance parameters through experimentation conducted at VIT University, Vellore, India. Distilled water was used as the working fluid. Maximum efficiency of 39.12% was acquired at 451.6 W/m 2 of direct normal irradiance (DNI)for absorber tube with internal pin-fins and without glass tube (AFWGt ) compared to 8.15% obtained at same value of DNI and other conditions for simple absorber tube without glass cover (AWGt ). Cylindrical parabolic trough available at the university was utilized, providing the basis for designing and fabrication of the tubes. Plots for varying mass flow rate at interval of 10 minutes were made against instantaneous thermal efficiency and heat utilized, for direct normal irradiance vs. temperature difference across the tubes and instantaneous thermal efficiency. Through the experimentation conducted, better performance was procured compared to earlier works. Thus, the proposal infers that absorber tube with internal fins has good scope for its application, both domestically as well as industrially. It also calls for further research and development of proposed techniques so as to achieve better performance curves.